Indigenizing the Teaching of Quebec and Canadian History at the Secondary and University Levels: Between Willingness, Epistemological Obstacles and Identity-Related Tensions - Moisan, Sabrina; Maltais-Landry, Aude; Hirsch, Sivane (Journal of the Canadian Association for Curriculum Studies, 2023)
The Truth and Reconciliation Commission of Canada’s (TRC) Call to Action 62 (2012), which focuses on education for reconciliation, directly challenges Canadian educational institutions, and more specifically the history classroom. While the education of non-Indigenous children is the responsibility of the provinces, it seems that Quebec is moving slower than other provinces in the project of recognizing and including Indigenous perspectives and knowledges in the teaching of history. How can we explain this in relation to the specific contexts of Quebec’s settler colonial history? To answer this question, we asked individuals teaching Quebec and Canadian history at the secondary and university levels (n=46) about their position on the inclusion of Indigenous perspectives and knowledges in the teaching of their discipline and the courses of action they identified to implement the TRC’s calls to action. From this analysis, we perceived first of all a certain enthusiasm for the inclusion of Indigenous history in classrooms, but epistemological and identity-related obstacles also emerged that could explain the specificity (or particularity) of Quebec in the current project of Indigenization in Canada.